Biological risk indicators for recurrent non-specific low back pain in adolescents. Issue 3 (23rd February 2005) - Jones, M A; Stratton, G; Reilly, T; Unnithan, V B
Abstract : Objectives: A matched case-control study was carried out to evaluate biological risk indicators for recurrent non-specific low back pain in adolescents. Methods: Adolescents with recurrent non-specific low back pain (symptomatic; n  =  28; mean (SD) age 14.9 (0.7) years) and matched controls (asymptomatic; n  =  28; age 14.9 (0.7) years) with no history of non-specific low back pain participated. Measures of stature, mass, sitting height, sexual maturity (Tanner self assessment), lateral flexion of the spine, lumbar sagittal plane mobility (modified Schöber), hip range of motion (Leighton flexometer), back and hamstring flexibility (sit and reach), and trunk muscle endurance (number of sit ups) were performed using standardised procedures with established reliability. Backward stepwise logistic regression analysis was performed, with the presence/absence of recurrent low back pain as the dependent variable and the biological measures as the independent variables. Results: Hip range of motion, trunk muscle endurance, lumbar sagittal plane mobility, and lateral flexion of the spine were identified as significant risk indicators of recurrent low back pain (p<0.05). Follow up analysis indicated that symptomatic subjects had significantly reduced lateral flexion of the spine, lumbar sagittal plane mobility, and trunk muscle endurance (p<0.05). Conclusions: Hip range of motion, abdominal muscle endurance, lumbar flexibility, and lateral flexion of the spine were risk indicators for recurrent non-specific low back pain in a group of adolescents. These risk indicators identify the potential for exercise as a primary or secondary prevention method.